Mapping tasks to occupations using Philippine data - Ian Nicole Generalao (University of the Philippines, School of Economics (UPSE), 2019)
Treating occupations as bundles of tasks rather than discrete categories is the central idea upon which the "task approach" to labor market analysis is built. To apply the framework, this paper maps the 3,279 task characteristics of occupations using the International Standard Classification of Occupations 2008 (ISCO-08) to derive the task portfolios of 424 occupations listed under the Philippine Standard Occupational Classification (PSOC). These portfolios allow us to measure how intensive an occupation is in performing different tasks (e.g. non-routine analytical, non-routine interpersonal, non-routine manual, routine cognitive and routine manual). The main contribution of this paper is the task portfolios of the 424 occupations, which can be a starting point for further studies on the implications of automation, immigration, and international offshoring on employment and the returns to specific skills, not just in the Philippines but also for countries which base their local occupational codes to the ISCO.
Keywords: J24; J01; J20; 330; Tasks; Skills; Human Capital; Labor Market Data